Influence of β-glucan on nonspecific immunity and growth performance in weanling pigs - Jishu N Shi; T L Kielian; M M Chengappa; J E Smith; Frank Blecha; Steven S Dritz; Robert D Goodband; Jim L Nelssen; Michael D Tokach (Kansas Agricultural Experiment Station Research Reports, 1994)
Three experiments, using 344 pigs, were conducted to evaluate the influence of Î²-glucan (MacroGardâ„¢-S) on neutrophil and macrophage function, resistance to Streptococcus suis challenge, and growth performance in weanling pigs. Î²-glucan, when fed at inclusion rates of .05 and .1 %, did not influence neutrophil or macrophage function or increase overall growth performance. Similarly, .025% Î²-glucan did not alter neutrophil or macrophage bactericidal activity or production of superoxide anion. However, diets containing.025% Î²-glucan increased average daily gain, average daily feed intake, and pigs weights and decreased plasma haptoglobin levels on d 21. Unfortunately, pigs fed a diet containing .025% that exhibited increased growth performance were more likely to die after challenge with S. suis. These data suggest the existence of a complex interaction involving growth performance and resistance to S. suis in pigs fed .025% Î²-glucan. The interaction should be investigated further.; Swine Day, Manhattan, KS, November 17, 1994
Keywords: Swine day; 1994; Kansas Agricultural Experiment Station contribution; no. 95-175-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 717; Swine; Starter pigs; Î²-glucan; Growth